Book review: Anis Ur Rahmaan. Evolution of Town Planning in Pakistan: With a Specific Reference to Punjab Province. (March 2022) - Adeel, Muhammad; Mayo, Shaker Mahmood
Anis Ur Rahmaan. Evolution of  Town Planning in Pakistan: With a Specific Reference to Punjab Province (Xlibris Corporation), 2017, 330 pp, US$23.99 (Paperback). ISBN-10: 1543449018, ISBN-13: 978-1543449013.